Patient-reported outcomes in systemic AL amyloidosis with functional assessment of cancer therapy-general (FACT-G) and patient-reported outcomes measurement information system-global health (PROMIS-GH) in a real-world population. Issue 14 (6th December 2019) - Chakraborty, Rajshekhar; Rybicki, Lisa; Tomer, Jacqulyn; Samaras, Christy J.; Faiman, Beth M.; Valent, Jason; Majhail, Navneet S.
Abstract: We performed an observational study on health-related quality of life (HRQoL) in patients with AL amyloidosis diagnosed between 2012 and 2017 at our institution. A total of 81 patients were included, with a median age of 64 years. The mean FACT-G (Functional Assessment of Cancer Therapy-General) total score at baseline (≤2 months from diagnosis) was 74 (±15), compared to a normative score of 80 (±18) in the general U.S. population. Significant HRQoL deficit was noted only in the functional well-being (FWB) domain of FACT-G. Using PROMIS-GH (Patient-Reported Outcomes Measurement Information System-Global Health) at baseline ( n = 18), a greater deficit was noted in the global physical health (GPH) compared to global mental health (GMH) domain. FACT-FWB and PROMIS-GPH domain scores were able to significantly discriminate between revised Mayo stages. Development and validation of an amyloid-specific PRO instrument incorporating specific domains of interest is urgently needed to pursue patient-centered drug development.